Provider Payment Reforms for Improved Primary Health Care in Romania - Chukwuma, Adanna; Comsa, Radu; Chen, Dorothee; Gong, Estelle (World Bank, Washington, DC, 2021)
Romania faces high levels of amenable mortality reflecting, in part, the relatively low utilization rates of high-quality primary health care (PHC), particularly for non-communicable disease (NCD) prevention and treatment. Provider payment mechanisms do not reward the high-quality care provision and may incentivize bypassing of PHC for hospitals, exacerbating challenges presented by physical, financial, and social barriers to accessing essential care. This paper assesses provider payment mechanisms at the PHC level, by examining their design features and implementation arrangements, and exploring their implications for PHC performance in terms of access and quality of care. The authors conclude with policy recommendations to address the constraints identified. To increase the supply of preventative care and case management, the authors recommend that volume thresholds for fee-for-service payments reflect both the number of enrollees and physicians in a practice; laboratory tests required for case management be reduced in scope and their costs be reimbursed; and the law on health care reform be amended to enable the introduction of new payment mechanisms, such as performance-based payments. To expand the scope of PHC and strengthen care coordination with hospitals, periodic reviews by physician commissions should aim to expand the scope of PHC care in line with provisions in other European Union (EU) countries for ambulatory-care sensitive conditions; capitation payments should be adjusted for gender and historical service use to reduce incentive for over-referrals; and payment mechanisms that reward coordination of care, including bundled payments, should be introduced. To establish an enabling environment for provider payment reforms, health information systems should be strengthened by unifying diagnosis coding, establishing quality standards, and ensuring referral module functionality; payment reforms should be informed by extensive consultations with providers at all service delivery levels; and PHC spending should be increased to support higher reimbursement levels for providers and match expenditure levels in high-performing EU health systems.